PERANCANGAN ALAT BANTU KERJA BERDASARKAN ANALISIS ERGONOMI DI BAGIAN MANUAL HANDLING PT. XYZ - Baeri, La Ode Muhammad Fardhan Sabil; Widodo, Lamto; Sukania, I Wayan (Universitas Tarumanagara, 2025)
In the printing industry, ergonomic factors are often overlooked despite their significant impact on worker health and productivity. PT XYZ, as a packaging and carton printing company, is facing musculoskeletal disorders (MSDs) complaints in workers in the manual handling section due to non-ergonomic workstation design. This study aims to identify ergonomic risk factors, analyze MSDs complaints, and design ergonomic workstation improvements. The methods used include Nordic Body Map (NBM) for complaint mapping, Rapid Entire Body Assessment (REBA) for work posture analysis, and Workplace Ergonomic Risk Assessment (WERA) for ergonomic risk evaluation. The NBM questionnaire shows that the body parts of the 1st and 2nd shift workers who predominantly experience pain complaints are pain in the back, left hand and right knee. While the REBA method obtained a value of 9 in the most extreme posture which means high risk and needs improvement. While in WERA the final score is 34 which means that the tasks performed by workers need to be investigated and needed for improvement. Therefore, the design of work tables and work chairs is carried out to improve the work posture of PT XYZ workers. This design is tailored to the needs of workers at PT XYZ so as to reduce the risks that are likely to occur.